HIGHER EDUCATION RANKING AND QUALITY ASSURANCE: ISSUES AND CRITICAL ASSESSMENT (GENERAL PROBLEM) - Muhammad Shohib Wildan (Universitas Islam Sultan Agung, 2018)
University rankings and quality assurance have become a widespread phenomenon in an increasingly competitive world of higher education. They differ with regard to their aims, objectives, target groups, and to their relationship to quality assessment. Generally, rankings are the result of an external assessment of the performance of higher education institutions; they enable transparency about systems of higher education. This paper discusses the relationship of rankings and quality assurance on an institutional and a system level. The discussion of the issue includes pros, cons of arguments and assertions following by conclusion and recommendation. A clear conception of the differences between rankings and other forms of assessment of higher education institutions helps to understand the usefulness as well as the limitations of rankings and helps to prevent false or unrealistic expectations of rankings. The discussion also included the critical issues and assessment about the true meaning of quality assurance as well as the ranking in higher educational institution.University rankings and quality assurance have become a widespread phenomenon in an increasingly competitive world of higher education. They differ with regard to their aims, objectives, target groups, and to their relationship to quality assessment. Generally, rankings are the result of an external assessment of the performance of higher education institutions; they enable transparency about systems of higher education. This paper discusses the relationship of rankings and quality assurance on an institutional and a system level. The discussion of the issue includes pros, cons of arguments and assertions following by conclusion and recommendation. A clear conception of the differences between rankings and other forms of assessment of higher education institutions helps to understand the usefulness as well as the limitations of rankings and helps to prevent false or unrealistic expectations of rankings. The discussion also included the critical issues and assessment about the true meaning of quality assurance as well as the ranking in higher educational institution.